Lighting the way forward: The bright future of photonic integrated circuits - M.A. Butt; B. Janaszek; R. Piramidowicz (Sensors International)
Integrated optics, a key photonics technology, has major implications for telecommunications, sensing, and computing. By integrating optical elements like lasers, modulators, and detectors onto a single chip, it enhances performance while reducing the size, weight, and power of optical systems. With potential applications in 5G, data centres, quantum communication, and AI, integrated optics is crucial for future communication technologies. Its synergy with quantum information and machine learning opens innovation pathways. This review explores recent advancements in optical platforms, highlighting ongoing research and developments that are driving technological progress in this field. The analysis provides an in-depth scrutiny of recent developments, shedding light on the dynamic terrain of optical innovations and highlighting the strides made in pushing the boundaries of technology.